Crença de grupo : uma introdução à epistemologia coletiva - Ruivo, José Leonardo Annunziato (2017)
Since the late 1980’s, we can notice a growing interest on the part of analytic philosofers in questions concerning the nature of the social world. This trend influenced some philosophers to start a systematic discussion about the relationship between typically epistemic concepts (such as belief, justification, and knowledge) and their relationship with the social world. The present essay belongs to this trend in the branch known as collective epistemology (in accordance with Margaret Gilbert’s 2004 terminology), that studies the semantics, ontology, psychology, and epistemology of collective entities. Our central problem is built around the following question: to say that a group G believes that P is the same as saying that most of the individuals, members of G, believe that P? In the first chapter, we will present an introduction of the main questions in the field. In the second chapter it will be argued that those who answer positively to the central problem assume some form of individualism because the collective entity ‘group’ cannot occupy the place of subject in ascriptions of belief. This subject individualism is a combination of two arguments: group anti-psychologism and group anti-mentalism. The third chapter is composed by three different sections. In the first section, we will present Margaret Gilbert’s model of anti-subject individualism. The second section concerns the debate between Gilbert’s model and a model of acceptance, as we call it. In the third part we will show how Christian List and Philip Pettit’s model (2011) fill some important gaps left by Gilbert’s model. As a conclusion, we arrive at a negative answer to our central question, that is, we affirm that a group G believes that P even if most of individuals, members of G, don’t believe that P.